2018
DOI: 10.1016/j.jor.2018.08.028
|View full text |Cite|
|
Sign up to set email alerts
|

Electromagnetic distal targeting system does not reduce the overall operative time of the intramedullary nailing for humeral shaft fractures

Abstract: The use of the EM distal targeting system doesn't reduce the overall operative time of the humeral shaft fracture fixation using IMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Neurovascular and/or tendon damage, breaking of the drill, and bleeding have been reported during the distal locking stage in the treatment of humeral shaft fractures with conventional nails. [ 3 , 7 , 8 , 17 , 18 ] The distal humerus is rich in neurovascular anatomic structures; therefore, percutaneous distal locking may cause risks during conventional nailing. In their studies on cadaveric bones, Rupp et al[ 19 ] reported that the radial nerve is in direct risk in conventional nailing techniques where the distal locking is placed from lateral to medial in accordance with nail design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurovascular and/or tendon damage, breaking of the drill, and bleeding have been reported during the distal locking stage in the treatment of humeral shaft fractures with conventional nails. [ 3 , 7 , 8 , 17 , 18 ] The distal humerus is rich in neurovascular anatomic structures; therefore, percutaneous distal locking may cause risks during conventional nailing. In their studies on cadaveric bones, Rupp et al[ 19 ] reported that the radial nerve is in direct risk in conventional nailing techniques where the distal locking is placed from lateral to medial in accordance with nail design.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are few studies reporting the results of electromagnetic systems in patients who underwent intramedullary nailing for humerus fractures. [ 8 , 17 , 18 ] Persiani et al[ 8 ] compared the electromagnetic system and freehand technique in terms of the time elapsed during the distal locking and exposure to radiation and the authors reported that the electromagnetic system significantly reduces the duration of distal locking and exposure to radiation, while causing additional cost. Antonini et al[ 17 ] reported an average distal locking time of 5.8 minutes for a single screw in their study using the electromagnetic system for humerus, femur, and tibia fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Нельзя не отметить высокую стоимость оборудования для реализации данных способов. По данным Lawrence Camarda и соавт., использование электромагнитных устройств для блокирования не уменьшает продолжительность операции по сравнению с техникой «свободной руки» [15]. При применении данного способа погрешность, то есть количество неправильно просверленных отверстий, по данным A. Allard, составляет 21,6% [16].…”
Section: основная группа контрольная группаunclassified
“…Although many studies focus on the use of EM in lower extremity fractures, there are few studies that compare the distal locking technique with intramedullary humeral nailing [32][33][34] . Camarda et al 35 reported that use of the EM technique was not able to significantly reduce the overall surgical time of the humeral shaft fixation. The finding was not in accordance with other studies on tibial or femoral fractures.…”
Section: Indispensable High Accuracy In Distal Locking Proceduresmentioning
confidence: 99%